2013
DOI: 10.1161/circulationaha.113.001584
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of Pacemakers

Abstract: Background-In developing economies, there are patients in whom pacemaker implantation is delayed because they cannot afford one. Reused devices have been a solution. To address concerns about safety, a cohort of consecutive patients implanted with a reused pacemaker was compared with a control group. Methods and Results-A cohort of 603 consecutive patients from 2000 to 2010 was studied in an ambispective noninferiority study. The study group patients (n=307) received resterilized pacemakers, and the control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 19 publications
1
29
0
2
Order By: Relevance
“…Despite this possible bias, respondents to this survey were geographically well representative of HRS physician members, as 74% of all HRS physician members practice in the United States and Canada (74% in this survey), 17% practice in highincome countries outside of the United States and Canada (14% in this survey), and 9% practice in lower-middle income countries and upper-middle (8% in this survey). 17 It should be noted that even countries considered by the World Bank as "upper-middle" and "lower-middle" income on a per-capita basis, such as India, 18 Mexico, 19 and the Philippines, 9 are potential beneficiaries of CIED reuse, and their views are captured in this survey. However, physicians practicing in World Bank "low-income" countries (i.e., per capita income of $1,035 USD or less), such as Haiti and North Korea, are not well represented in the HRS (0.03% of physician members), and none completed this survey.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Despite this possible bias, respondents to this survey were geographically well representative of HRS physician members, as 74% of all HRS physician members practice in the United States and Canada (74% in this survey), 17% practice in highincome countries outside of the United States and Canada (14% in this survey), and 9% practice in lower-middle income countries and upper-middle (8% in this survey). 17 It should be noted that even countries considered by the World Bank as "upper-middle" and "lower-middle" income on a per-capita basis, such as India, 18 Mexico, 19 and the Philippines, 9 are potential beneficiaries of CIED reuse, and their views are captured in this survey. However, physicians practicing in World Bank "low-income" countries (i.e., per capita income of $1,035 USD or less), such as Haiti and North Korea, are not well represented in the HRS (0.03% of physician members), and none completed this survey.…”
Section: Study Limitationsmentioning
confidence: 99%
“…A study by Nava et al [18] compared a cohort of consecutive patients implanted with a reused pacemaker with a cohort implanted with a new pacemaker. The authors concluded that reuse of pacemaker generators was not inferior to the use of new devices [18]. …”
Section: Discussionmentioning
confidence: 99%
“…35,36 Two metaanalyses have also demonstrated the safety and efficacy of pacemaker reuse. 37,38 The metaanalysis of 18 studies 38 39 Data regarding safety and efficacy of reuse of ICDs and biventricular pacemakers are less robust. In a single-center, retrospective study in India involving 81 indigent persons with mean follow-up of 824.9 days, the reused ICDs functioned normally and delivered life-saving therapies, without an increased risk for complications.…”
Section: Scientific Evidence Behind Reuse Of Cardiac Rhythm Control Dmentioning
confidence: 99%